Insurers' risk management as a business process: A prospective competitive advantage or not? - Danish Ahmed; Yuantao Xie; Umair Saeed Bhutta (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - Insurance companies exist to manage the risk of others, which is why they are perceived to be competitive in risk management (RM). Considering this, we investigate how different RM capabilities make insurers effective in RM. These capabilities include understanding risk and risk management (URRM), risk identification (RI), risk assessment and analysis (RAA) and risk monitoring (RMON) activities in insurance companies. In addition, the authors probe how these capabilities can jointly yield a competitive advantage for the insurance industry under the resource-based view (RBV) and dynamic capabilities perspective (DCP). Design/methodology/approach - The authors present a latent variable RM model for the insurance industry and employ structural equation modeling (SEM) to test the hypotheses. Furthermore, the authors also conduct confirmatory factor analysis (CFA) and convergent and discriminant validity analysis for model fit and invariance testing, respectively. Findings - The results show that insurers who investigated RM-related capabilities directly influence their risk management practices (RMPs). Moreover, improving these capabilities will make insurers more effective in managing the risks of others. Thus, RM as a business process will yield a competitive advantage for the insurance sector. The findings are supported by the theoretical insights presented by the RBV and DCP. Furthermore, the model also adheres to the convergent and discriminant validity cut-off values. Originality/value - To the best of the authors' knowledge, this is the first study examining insurers' RM practices as a source of a competitive advantage.
Keywords: 650; Competitive advantage; Developed and emerging markets; Dynamic capabilities perspective; Resource-based view; Risk management practices